Thermoregulation of Premature Infants during and after Skin-to-Skin Care - Heimann, K.; Ebert, A. M.; Abbas, A. K.; Heussen, N.; Leonhardt, S.; Orlikowsky, T. (Zeitschrift für Geburtshilfe und Neonatologie, 2013)
Providing normothermia is an important issue in daily routine care of premature neonates. We recently found with infrared thermography (IRT) a drop in skin temperature of premature babies after they were positioned from skin-to-skin care (SSC) back into the incubator. Since this did not disappear within 10 min, we wanted to find out how long it takes until the baby has fully warmed up after SSC and if the IRT measurements correlate with conventional rectal temperature?A prospective observational study was undertaken with 5 premature infants [3 male, median gestational age 28 weeks (25–29), median age at study 34 d (28–52), median birth weight 898 g (400–1 095), median weight at study 1 263 g (790–1 465)], temperature was determined with IRT (leg, back, arm, head, upper abdomen; diameter 1 cm, scale 0.00°C), comparison with 2 conventional sensors and rectal temperature. Temperatures were recorded every 2 min and displayed for 4 time points, namely at the beginning and the end of skin-to-skin care (SSC1, SSC2), as well as at the beginning and the end of a subsequent 60 min incubator period (I).A significant rise during SSC occurred while the cooling after SSC persisted during the complete incubator measurement time (I; p<0.05). Rectal temperature remained stable through the whole measuring period.While SSC in our setting led to an increase in temperature, the lack of compensation of peripheral heat loss in the incubator after 60 min may express an inadequate peripheral regulation of body temperature. This should be taken into account before routine care after SSC.
Keywords: infrared thermography; skin-to-skin care; thermoregulation; body temperature